Chernozems in Czechia: Soil properties, classification and environmental controls - Rojas, Jessica Reyes; Margoldová, Anna; Skála, Jan; Žížala, Daniel; Penížek, Vít; Hrdlička, Tomáš; Vaněk, Aleš; Zádorová, Tereza (Geoderma Regional, 2025)
Chernozems and related soils (chernozemic soils) represent an important part of the soil cover and soil organic carbon (SOC) pools in Czechia. Despite their importance, a comprehensive understanding of their variability, classification, and key environmental controls is still limited. This study, using an extensive database of almost 4000 soil profiles, describes the most important soil characteristics and their variability within and among the Czech chernozemic taxonomic units and identifies the dominant drivers that influence their properties and classification. Moreover, their position within the World Reference Base (WRB) 2022 is analysed. Overall, Czech chernozemic soils are characterised by deep humus horizons (mean = 56 cm) with mean SOC content of 1.25% and neutral pH (mean = 7). Hydromorphic chernozems show the deepest and SOC-richest humus horizons, while shallow and SOC-poor humus horizons are typical for eroded chernozems. Majority of studied profiles were classified within one of the mollic Reference soil groups in WRB, of which 43% were attributed to Chernozems. Luvisols (4%), Regosols (7%) and Calcisols (3%) were classified among clay illuvial or eroded profiles. Multivariate statistical analysis showed environmental factors dominating over individual soil properties. Substrate characteristics (texture and CaCO3 content), were the most important for the SOC content, outweighing the influence of climatic factors or terrain position. The latter predominantly affected humus horizon depth and was best suited to differentiate hydromorphic chernozems. Climatic factors controlled soil pH and distinguished clay illuvial soils. A broader understanding of these patterns must also consider the influence of historical land management and Holocene vegetation shifts which were beyond the scope of this study. •Chernozems are a key component of soil cover and carbon storage in Czechia.•They have a deep humus horizon with moderate SOC content and neutral soil pH.•The parent material outweighed the influence of climatic or terrain factors for SOC content.•Most of the profiles fit to one of the mollic Reference Soil Groups in WRB 2022.•Soil legacy data is valuable for studying the characteristics of chernozemic soils.